VALUE OF PANAI’ ON SOCIAL CAPITAL CONCEPTCULTURAL STUDY IN SOUTH SULAWESI - Silviyana Usman; Tenriwaru Tenriwaru (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2022)
This study aims to determine how to determine the value of panai' in the Bugis-Makassar ethnic community in South Sulawesi. This study uses a qualitative method with an ethnographic approach with narrative analysis techniques. The ethnographic approach is a qualitative research strategy in which the researcher investigates culture in the natural environment for a sufficiently long period of time to collect data. The data of this study were obtained from primary and secondary data. The results showed that to determine the amount of panai' there were several factors, namely social status, education level, physical factors of the prospective bride, food prices and social capital. The position of the panai' money is very burdensome for the men if the panai' money requested is too expensive. Panai money should be a form of positive attitude shown by men who have to work hard to provide panai money in order to woo the desired lover. In accounting, transparency and accountability of panai' money is very necessary for both candidates to maintain trust because the amount of money given must be known by the nuclear family of the prospective bride and groom and in its management it must be used according to its function.